Significance of maximum intensity projection technique of multimodal ultrasound imaging in differentiating follicular thyroid carcinoma from benign lesions - Gao, Wei; Chen, Yutong; Wu, Qiong (Frontiers in Oncology, 2024)
ObjectivePreoperative diagnosis for follicular thyroid cancer (FTC) remains challenging. The purpose of this study was to explore the maximum intensity projection (MIP) features, which can be utilized for reconstructing and characterizing the structure of microvascular in tissue, associated with FTC, and to explore the independent risk factors for FTC in combination with multimodal ultrasonography and blood indicators.MethodsThis single-center, prospective, single-blind, observational study included patients with suspected follicular thyroid carcinoma based on preoperative ultrasonography findings. All patients underwent routine ultrasonography, contrast-enhanced ultrasonography (CEUS), and correlated blood indexes tests. Offline MIP reconstruction of the CEUS images was performed. The tumor was histologically diagnosed postoperatively. Multivariable logistics regression was utilized for analyzing MIP characteristics combined with multimodal ultrasonography and preoperative blood indicators to identify independent risk factors for FTC.ResultsIn this study, 61 thyroid nodules were finally included according to the atretic criteria. (1) Compared with traditional color profile ultrasonography and CEUS, MIP technology can provide more information regarding microvascular characteristics inside thyroid tumors. The short, rod-like, crossed, curved and firework-like features of MIP images revealed statistically significant differences between the benign and malignant groups. (2) Multivariable logistic regression analysis indicated that the firework-like MIP characteristics of microvascular, thyroglobulin (Tg) level and vessel intensity (VI) value were independent risk factors for malignancy.Conclusion(1) MIP technology has potential applications in the differential diagnosis of follicular thyroid carcinoma from benign lesions. (2) Firework MIP microvascular characteristics, Tg values and VI values can serve as parameters for the differential diagnosis of follicular thyroid carcinoma from benign lesions. This study provides a novel approach idea for preoperative multimodal differentiation of follicular thyroid carcinoma from benign lesions.